Tthe participating environmental education like a means for the natural environment´s protection and conservation - Liuba Berra-Hernández (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2013)
The present work approaches a problem of great interest for the society and for the world in general, the Environmental Education, a way to put end to the global environment problems. Hence, the objective of the work is to let know the population some environmental weaknesses and strengths and to include them in the search of solutions. The article is based on the results of observations, surveys and interviews carried out to the residents of Sandino, as well as on the great deal bibliography searching. The obtained results in the carried out diagnosis allowed to verify that the level of environmental knowledge in the residents is not the appropriate one, because they don't know the main environmental problems of the county neither of the municipality. For that reason Revista electrónica de Ciencia y Tecnología en la Cultura Física it is indispensable the necessity of alternatives searching that propitiate attitude changes in the different population groups that favor the environment and its development, where the study of environmental indicators constitutes an effective way to achieve the proposed objectives.